2019
DOI: 10.1016/j.aninu.2019.04.003
|View full text |Cite
|
Sign up to set email alerts
|

Fermentation characteristics of resistant starch, arabinoxylan, and β-glucan and their effects on the gut microbial ecology of pigs: A review

Abstract: Dietary fibers (DF) contain an abundant amount of energy, although the mammalian genome does not encode most of the enzymes required to degrade them. However, a mutual dependence is developed between the host and symbiotic microbes, which has the potential to extract the energy present in these DF. Dietary fibers escape digestion in the foregut and are fermented in the hindgut, producing short-chain fatty acids (SCFA) that alter the microbial ecology in the gastrointestinal tract (GIT) of pigs. Most of the car… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
46
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
2
1

Relationship

2
8

Authors

Journals

citations
Cited by 80 publications
(51 citation statements)
references
References 122 publications
(215 reference statements)
1
46
0
Order By: Relevance
“…The AVF for this application is often derived from micronized wheat envelopes (bran) comprised of a variety of carbohydratesmainly hemicellulose molecules-composed of β-(1,4)-linked-glucose, -mannose, and -galactose [33]. However, we hypothesise that the degradation of these molecules in the hindgut is sometimes assisted with enzymatic aids such as β-D-glucanase but tends to liberate the mycotoxins that have interacted with this vegetal carbohydrate fraction that is then further absorbed as an energy source for the host [34]. This degradation progressively reduces the interactions, resulting in the release of bound mycotoxins, making them bioavailable to the host once again and thus counterbalancing the competition between the feed matrix and the adsorbent for access to the mycotoxin.…”
Section: Discussionmentioning
confidence: 98%
“…The AVF for this application is often derived from micronized wheat envelopes (bran) comprised of a variety of carbohydratesmainly hemicellulose molecules-composed of β-(1,4)-linked-glucose, -mannose, and -galactose [33]. However, we hypothesise that the degradation of these molecules in the hindgut is sometimes assisted with enzymatic aids such as β-D-glucanase but tends to liberate the mycotoxins that have interacted with this vegetal carbohydrate fraction that is then further absorbed as an energy source for the host [34]. This degradation progressively reduces the interactions, resulting in the release of bound mycotoxins, making them bioavailable to the host once again and thus counterbalancing the competition between the feed matrix and the adsorbent for access to the mycotoxin.…”
Section: Discussionmentioning
confidence: 98%
“…However, all DF is not created equal and its efficacy to modulate microbial taxa, diversity, and composition is dependent on DF composition, solubility, and concentration [ 33 , 34 ]. In general, soluble DF and non-digestible oligosaccharides are fermented at a faster rate compared to insoluble DF [ 35 , 36 ] and are associated with reducing pathogenetic microbes, increasing microbial diversity, and improving the proliferation of ‘beneficial’ microbes [ 37 , 38 ]. In contrast, swine diets are largely composed of poorly fermentable insoluble DF emanating from cereal grains and industrial co-products [ 8 , 39 ].…”
Section: Discussionmentioning
confidence: 99%
“…Arabinoxylan, a water-soluble NSP found in high concentrations in wheat, has antinutritive effects, such as being a pro-inflammatory agent and increasing digesta viscosity, but research has shown derivatives of these compounds with appropriate source and amount may have beneficial effects [ 104 , 105 ]. Yacoubi et al [ 106 ] isolated arabinoxylans from wheat and added them to a broiler chick diet with a multienzyme, which created short-chain arabinoxylan polysaccharides.…”
Section: Effects Of Dietary Fiber On the Immune Systemmentioning
confidence: 99%